Respostas

  • Usuário do Brainly
2014-06-18T11:38:09-03:00
{2x + 3y = 19
{x - y = - 3

x - y = - 3
x = - 3 + y

2x + 3y = 19
2 . (- 3 + y) + 3y = 19
- 6 + 2y + 3y = 19
2y + 3y = 19 + 6
5y = 25
y = 25/5
y = 5

x = - 3 + y
x = - 3 + 5
x = 2

S = {2, 5}
3 5 3
2014-06-18T11:50:00-03:00
(a) 2x+3y = 19 ===>>> 2x + 3y = 19
(b) x-y = -3 (3) ===>>> 3x - 3y = -9
                                    5x = 10 ==>> x = 10/5 => x = 2
- Substituindo x = 2, em quaisquer das equações:
x - y = -3 => 2 - y = -3 => -y = -3 - 2 => -y = -5 (-1) => y = 5
3 3 3